2002
DOI: 10.1021/jm0201417
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Dependent Inhibition of HIV-1 Integrase

Abstract: Human immunodeficiency virus type 1 integrase (HIV-1 IN) is an essential enzyme for effective viral replication. Therefore, IN inhibitors are being sought for chemotherapy against AIDS. We had previously identified a series of salicylhydrazides as potent inhibitors of IN in vitro (Neamati, N.; et al. J. Med. Chem. 1998, 41, 3202-3209.). Herein, we report the design, synthesis, and antiviral activity of three novel mercaptosalicylhydrazide (MSH) derivatives. MSHs were effective against the IN catalytic core dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 45 publications
6
59
2
Order By: Relevance
“…3Ј Processing, strand transfer, and disintegration can be independently measured in biochemical assays using specific oligonucleotides (Figs. 1A, 2A, and 3A) (Marchand et al, 2001 , is required for integrase activity in vitro (Engelman and Craigie, 1995 (Grobler et al, 2002;Neamati et al, 2002;Marchand et al, 2003), all assays were performed in the presence of either Mg 2ϩ or Mn 2ϩ . .…”
Section: The 7-hydroxy Group Is Essential For Inhibition Of Hiv-1 Intmentioning
confidence: 99%
“…3Ј Processing, strand transfer, and disintegration can be independently measured in biochemical assays using specific oligonucleotides (Figs. 1A, 2A, and 3A) (Marchand et al, 2001 , is required for integrase activity in vitro (Engelman and Craigie, 1995 (Grobler et al, 2002;Neamati et al, 2002;Marchand et al, 2003), all assays were performed in the presence of either Mg 2ϩ or Mn 2ϩ . .…”
Section: The 7-hydroxy Group Is Essential For Inhibition Of Hiv-1 Intmentioning
confidence: 99%
“…[4][5][6][7] It has become apparent over recent years that inhibition of the HIV-IN ST reaction is the primary key to the effective suppression of viral replication in vivo. 8 Small molecules, on the other hand, which inhibit the in vitro activity of HIV-IN by interfering with DNA binding or the 3P reaction alone, generally lack antiviral activity.…”
Section: +mentioning
confidence: 99%
“…Differences in the coordination properties of Mg 2ϩ and Mn 2ϩ ions may result in different conformational changes in the IN catalytic core. This may account for differences in the specificity of HIV-1 IN interactions with substrate DNA (1,2), inhibitors (3,12), and the nucleophiles used to carry out 3Ј-end processing (13). As IN is more sensitive to the structure of molecules interacting with its catalytic core in the presence of magnesium ions, it has been suggested that the catalytic core of this molecule is more rigid in the presence of magnesium ions, as reported for other magnesium-dependent enzymes (1).…”
mentioning
confidence: 99%